Our Right to the Pleasure of Falling in Love - Torras-Gómez, Elisabeth; Puigvert, Lídia; Aiello, Emilia; Khalfaoui, Andrea (Frontiers in Psychology, 2020)
The social impact of psychology on the field of human sexuality is extensively wide. From Freud to Masters and Johnson, many are the research which have broken barriers and provided citizens with new knowledge to improve their lives. One of the lines of research which are now contributing to this social impact from psychology is that of the dominant coercive discourse (Gómez, 2015), which portrays power relationships as exciting and egalitarian relationships as convenient. Drawing from this theory, the aim of this research is to shed light on the influence of the coercive discourse on women’s pleasure in their intimate relationships. In an exploratory study, women between 20 and 29 years-old were interviewed under the communicative methodology. Results show three main findings. First, participants who reject the coercive discourse find pleasure in egalitarian relationships. On the contrary, participants who had coerced relationships acknowledge a lack of excitement in egalitarian relationships, while associating pleasure to the power nature of the former. Finally, some participants who initially had coerced sexual-affective relationships were able to disassociate pleasure from coerced relationships and break with them. Moreover, these women claim to feel more pleasure in their new egalitarian relationships. These findings open a new path of research that unveils the lack of pleasure in coerced relationships and vindicates our right to the pleasure of falling in love.